A diptych of dilemma: Becoming an artist and a teacher. (1st June 2017) - MacDonald, Abbey
This article examines factors identified as influencing teachers' capacity to maintain arts practice upon beginning teaching. In exploring the storied experiences of three artists and teachers, a discussion unfolds to examine the ways that artist and teaching practices interact, and the implications this interaction has upon the beginning teachers' transition into professional practice. A hybridized methodology has been adopted, where methods integral to autoethnography, narrative inquiry and a/r/tography are drawn together to generate a series of intricately layered stories of becoming artists and teachers. From these storied insights, the factors that emerged as critical to becoming are the beginning teachers' perceptions and management of time, and their capacity to appropriately prioritize art and teaching practices over each other. The implications of these factors indicate a need for beginning teachers to better understand and acclimatize to the demands of becoming a teacher before attempting to resume high levels of artistic output.